Analysis Methods for Computerized Forecasting in the Athletes’ Sportive Performances for Term of the Competitional Period - Raţă, E.; Milici, L. D. (Elektronika ir Elektrotechnika, 2009)
A computerized method of analyzing and forecasting of sports performances of athletes in the competition season is presented. There are analyzed the most frequently utilized functions of approximation and the way that these allow the most accurate evaluation. It is established, using real data and error estimation, that the exponential function is the one indicated in these types of evaluations and conclusions are made over the errors obtained for each interpolation method used. Ill. 1, bibl. 9 (in English; summaries in English, Russian and Lithuanian).